The Influence of Learning Strategies and Achievement Motivation on Learning Outcomes of Understanding Sociological Concepts at SMA Negeri 1 Masohi, Central Maluku Regency - Arnold Sahalessy; Hermelina Abarua (Peneliti.net, 2021)
This study aims to (1) examine the differences in learning outcomes of understanding sociological concepts between groups of students who are taught withlearning strategies expository and learning strategy Problem based learning (2) Testing the difference in learning outcomes of understanding the concept of sociology between groups of students who have high and low achievement motivation (3) Testing the significance of the interaction between learning strategies and achievement motivation on learning outcomes of understanding the concept of sociology. The method used is a quasi-experimental design with a 2 x 2 factorial. This study concludes that the first. there is a significant difference in learning outcomes of understanding sociological concepts between groups of students who are taught with problem based learning learning strategies andlearning strategies expository as evidenced by the average problem based learning learning strategy is = 81 and the averagelearning strategy expository = 70 while F testcount = 113.48 > 4.02 Ftable at the confidence level = 0.05. Second. There is a significant difference in learning outcomes of sociology concepts between groups of students who have high and low achievement motivation as evidenced by the average learning outcomes of high achievement motivation groups = 76.59 and learning outcomes of understanding sociological concepts in students who have low achievement motivation is = 74.46. With the results of theF testcalculated = 4.36 > 4.02 Ftable at the confidence level = 0.05